2013
DOI: 10.1007/s10681-013-0881-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of resistance to late leaf spot in interspecific groundnuts

Abstract: Late leaf spot (LLS), caused by Phaeoisariopsis personata, is an important foliar fungal disease of groundnut (Arachis hypogaea L.), which causes significant economic losses globally to the crop. Inheritance of resistance to LLS disease was studied in three crosses and their reciprocals involving two resistant interspecific derivatives and a susceptible cultivar to refine strategy for LLS resistance breeding. The traits associated with LLS resistance, measured both in the field and under controlled conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…In post-rainy 2018, the population (620) was screened in light chamber (Controlled facility) using the detached leaf assays which is a rapid screening technique for LLS [27,28]. A completely randomized (CRD) experimental design with two replications was used.…”
Section: Screening For Lls Resistance Using Detached Leaf Assay In Light Chambermentioning
confidence: 99%
“…In post-rainy 2018, the population (620) was screened in light chamber (Controlled facility) using the detached leaf assays which is a rapid screening technique for LLS [27,28]. A completely randomized (CRD) experimental design with two replications was used.…”
Section: Screening For Lls Resistance Using Detached Leaf Assay In Light Chambermentioning
confidence: 99%
“…Detached, healthy groundnut leaves rooted in ster ile sand in trays are inoculated with a concentration of 30,000 spores ml-1 for LLS and 105 urediniospores ml-1 for rust, followed by incubation in the growth chamber at 24 °C temperature and 85 % relative humidity and a 12 h light/12 h dark regime. LLS disease development is determined every 2 days from 5 to 37 days after inocu lation and observations are recorded on incubation period (days), latent period (days), lesion number, lesion diameter (mm) and leaf area damage (%) (Janila et al 2013). Rust pustules appear some 10 days after inoculation on susceptible geno types.…”
Section: Screening For Foliar Fungal Diseasesmentioning
confidence: 99%
“…Kimber and Paull (2011) studied the genetics of resistance to Cercospora leaf spot in Feba bean and reported a monogenic dominant gene control leaf spot resistance with resistance dominant over susceptibility. Pasupuleti et al (2013) reported that late leaf spot in groundnut was governed by a combination of both, nuclear and maternal gene effects. Little or no information is available on the genetics of CLS resistance in Nigerian cowpea varieties.…”
Section: Introductionmentioning
confidence: 99%